2012
DOI: 10.1007/s00244-012-9763-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Changes of Metal Availability in Soil. Part I: Comparing Sludge-Amended With Metal-Spiked Soils

Abstract: Sewage sludge application to soils is regulated by its total metal content. However, the real risk of metals is determined by the fraction that is biologically available. The available fraction is highly related to the strength of metal binding by the matrix, which is a dynamic process. The evaluation of the fate of metals in time can contribute increased accuracy of ecological risk assessment. Aiming to evaluate short-term changes in metal availability when metals were applied to soil directly (metal-spiked) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Adding organic matter to these types of soils leads to a descent in the assimilable metal content, as this is capable of forming strong bonds with metals and therefore retain them firmly in the soil (Kabata-Pendias, 2001). Different studies have shown that adding amendments made of waste materials reduces the assimilable metal content in the soil (Brown et al, 2003;Natal-da-Luz et al, 2012). The increased content of organic matter provided by the residue causes an increase in the sorption capacity of heavy metals in soil (Kocasoy and Güvener, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Adding organic matter to these types of soils leads to a descent in the assimilable metal content, as this is capable of forming strong bonds with metals and therefore retain them firmly in the soil (Kabata-Pendias, 2001). Different studies have shown that adding amendments made of waste materials reduces the assimilable metal content in the soil (Brown et al, 2003;Natal-da-Luz et al, 2012). The increased content of organic matter provided by the residue causes an increase in the sorption capacity of heavy metals in soil (Kocasoy and Güvener, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Due to the intensification of water quality requirements and more rigorous environmental laws in Europe, the production of biosolids has sharply increased in recent years. , The main management options include incineration, landfill sites, and application to agricultural lands as soil amendment . The use of biosolids in agriculture is widely practiced all over the world since it is the most economical option allowing the recycling of plant nutrients and organic matter. However, this practice can be potentially harmful to the environment because biosolids contain high concentrations of toxic heavy metals. , Copper, nickel, and zinc are essential micronutrients required for plant nutrition and their addition with biosolids may be beneficial, but they are also potential environmental contaminants and will persist in the soil long-term if added in excess. , The fate of potentially toxic elements following short and long-term application of biosolids is well reported in the literature but this issue remains strongly controversial within the scientific community. Some published data have shown that the long-term biosolid spreading would result in the release of metals into the soil due to organic matter mineralization; it is the “time bomb hypothesis”. ,, Other authors have suggested that the long-term application of biosolids would present no environmental risk, due to the high adsorption capacity of mineral phases within biosolids; it is the “protection hypothesis”. ,, Consequently, to better predict the environmental fate and mobility of contaminants, it is critical to study the speciation of heavy metals in biosolid-amended soils.…”
Section: Introductionmentioning
confidence: 99%